The Diversity of Mosquito Species (Diptera: Culicidae) Around Cowsheds in Tanah Miring District, Merauke - Desmina Kristiani Hutabarat; Apri Irianto; Nurcholis Nurcholis; Yolanda Gebse; Jefri Sembiring (JURNAL TRITON, 2026)
Tanah Miring District is one of the areas in Merauke Regency with a high cattle population. The landscape of Tanah Miring District is characterized by lowlands with slopes of 0-3%, dominated by swampy areas and grazing fields for livestock, such as cattle. One factor affecting cattle productivity is the presence of disease vectors such as mosquitoes. This study aims to provide information on the diversity of mosquito species found around cattle pens as preliminary data to support cattle productivity, maintenance, and care programs in controlling cattle disease vectors. The research method employed was the around-cattle collection method, conducted around cattle pens in three villages within the Tanah Miring District. The mosquitoes captured were then identified using a stereo microscope and a key for identifying mosquito genera and species at Laboratory 1 of the Faculty of Agriculture, Musamus University. Data on mosquito species and numbers of female mosquitoes were obtained for further analysis of diversity, evenness, and dominance indices. Based on mosquito collection results in cattle pens in Tanah Miring District, 41 species and 10 genera of mosquitoes were found. The species Coquellittida nigrochracea and Coq. ochracea were the most commonly found species around cattle pens in Tanah Miring District. The mosquito species diversity index fell within the moderate category, with an even distribution of mosquito species, and the dominant mosquito species ranged from 0.1 to 0.3. This indicates that mosquito species are very less prevalent around the cattle shed in the Tanah Miring District, Merauke. The presence of mosquitoes is commonly found on the roots of aquatic plants, namely Coq. nigrochracea and Coq. ochracea, which are also found around the cattle shed, indicates the need for mosquito vector control efforts by maintaining cleanliness around the cattle shed, such as clearing the grass and aquatic plants.